(untitled) (Research, Society and Development, 2022)
Introduction: Urinary tract infection (UTI) is a common disease in the community, especially in the elderly, due to several factors that favor its development and makes treatment difficult. Due to the atypical clinical presentation in this population, the diagnosis becomes more difficult, leading to more severe forms of the disease. A rapid and assertive choice of an antimicrobial therapy becomes essential to restore the health of the elderly. Objective: The purpose of the present study was to review the literature on community-based UTI with a focus on the elderly population, including the analysis of antimicrobial susceptibility. Methodology: This is a literature review, in which articles from the Google Scholar, Scielo, Nature and Science Direct databases and dissertations/thesis and literary works were used in the period from 2015 to 2021. The articles included were available online in Portuguese, English or Spanish and in full text, which reported UTI in the elderly in the community, epidemiological aspect and antimicrobial susceptibility. Results: Among the selected articles, Escherichia coli was the agent with the highest incidence, followed by Klebsiella spp, Proteus mirabilis and Enterococcus spp. and first-generation cephalosporins, and presenting greater sensitivity to beta-lactams, cephalosporins, and carbapenems. Conclusion: Escherichia coli was the most prevalent uropathogen, with different susceptibility indices according to the class of antimicrobials.